2016
DOI: 10.1002/rcs.1770
|View full text |Cite
|
Sign up to set email alerts
|

Technical feasibility and safety of an intraoperative head‐up display device during spine instrumentation

Abstract: A wearable head-up display can benefit current neuronavigation systems, but larger, outcomes-based trials are needed. Higher processing speed would allow streaming of higher resolution images. Along with an enlarged display, these may significantly improve utilization of this technology. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 11 publications
0
71
0
Order By: Relevance
“…It can project any image-such as navigation or neuromonitoring-directly in front of the surgeon's eyes (in other words, to his glasses), eliminating the need to look away from the surgical site. 61 Project Tango is software capable of 3D visuospatial scanning and reconstruction. This can be used to view the surgical area of interest and display useful AR imagery, such as tumor overlays, pedicle screw trajectories, or nearby vital anatomy.…”
Section: 41mentioning
confidence: 99%
“…It can project any image-such as navigation or neuromonitoring-directly in front of the surgeon's eyes (in other words, to his glasses), eliminating the need to look away from the surgical site. 61 Project Tango is software capable of 3D visuospatial scanning and reconstruction. This can be used to view the surgical area of interest and display useful AR imagery, such as tumor overlays, pedicle screw trajectories, or nearby vital anatomy.…”
Section: 41mentioning
confidence: 99%
“…demonstrated that fewer head movements were required when Google Glass was used while performing ultrasound‐guided central line placement. Yoon et al . performed 3‐dimensional (3D) image‐guided spine instrumentation in 10 patients with the assistance of a wearable head‐up display, which resulted in less time spent placing pedicle screws as well as an overall improved operative experience for the surgeon based on post‐operative surveys.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Our group previously demonstrated use of this novel device in transferring neuronavigation images onto head-up displays for procedures including image-guided pedicle screw placement, ventriculoperitoneal shunt placement, and supratentorial meningioma resection. [3][4][5] In all cases, the surgeons wore Google Glass (X, Mountain View, California) to view navigation images side-by-side while operating. Furthermore, head-up displays eliminated the need for surgeons to look away from the surgical field and allowed the surgeon to continue directing his attention to the primary task.…”
Section: Elsharkawy H Elmentioning
confidence: 99%